Analisis Pengaruh Motivasi Kerja, Rotasi Kerja dan Kepuasan Kerja Terhadap Kinerja Pegawai di Dinas Perumahan, Kawasan Permukiman dan Pertanahan Kabupaten Alor - Agustinus M. Lakalau (Jurnal Ilmiah Wahana Pendidikan, 2023)
Employee performance is the result of work and work behavior that has been achieved in completing the tasks and responsibilities assigned to employees at the Housing, Settlement Areas and Land Office of Alor Regency. This study aims to determine the effect of work motivation, job rotation and job satisfaction on employee performance either partially or simultaneously. This research was conducted on civil servants at the Department of Housing, Settlement Areas and Land Affairs of Alor Regency as many as 42 people. Sampling was carried out using a saturated sample technique in which the entire population was sampled. Data collection was carried out using observation, interviews, questionnaires and documentation while data analysis techniques used descriptive statistics, research instrument tests consisting of validity and reliability tests, classical assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests and linearity tests then to determine the effect of independent variables on the dependent variable used partial test and simultaneous test. The results showed that partially the work motivation variable had an effect on employee performance variables at the Housing, Settlement Areas and Land Offices of Alor Regency as evidenced by the significant value of the t-test variable work motivation of 0.046 less than the alpha value (0.046 ˂ 0.05). Partially, the work rotation variable has an effect on employee performance variables at the Housing, Settlement Areas and Land Offices of Alor Regency, as evidenced by the significant value of the t test for the work rotation variable of 0.026, which is less than the alpha value (0.026 ˂ 0.05). Partially, the job satisfaction variable has an effect on employee performance variables at the Housing, Settlement Areas and Land Offices of Alor Regency as evidenced by the significance value of the t-test variable work rotation of 0.034 which is less than the alpha value (0.034 ˂ 0.05). Simultaneously the variables of work motivation, job rotation and job satisfaction affect employee performance variables at the Department of Housing, Settlement Areas and Land Affairs of Alor Regency as evidenced by the significance value of the F test of 0.015, smaller than the alpha used (0.015 ˂ 0.05). The magnitude of the influence of work motivation, job rotation and job satisfaction variables on employee performance variables at the Housing, Settlement Areas and Land Office of Alor Regency is 0.237 or 23.7%.